Scientific production and nurses' training: a methodological approach to the state of the art monographs (Research, Society and Development, 2019)
The article objectified to analyze the state of the art of the nursing course leaving of the monographic productions of diverse especialties, with focus in the used methodological procedures for the elaboration of the monographs of the course of Nursing of the Center of Superior Studies of Rafts, campus of the State University of the Maranhão. With the conclusion of 06 (six) groups, and in compliance with the rules of the Ministry of the Education, the Pedagogical Project of the related course makes use concerning the requirement of elaboration of a monograph as work of course conclusion. From the lived deeply experiences and of dialogues with egresses, it was awakened curiosity in knowing the used methodological procedures for the elaboration of the work in question. Hypothetically, what one perceives is that the methodology applied in the form to understand the dimension of the research is not absorbed satisfactorily for the graduating. Ahead of this, to reach the objectives of this study, we use as source the bibliographical, documentary, quantitative research, with the use of resources of the descriptive and qualitative statistics in regards to the analysis of content, considered for Bardin. The reading of 125 (one hundred and twenty and five) monographs was carried through, what it corresponds to a sample of 69,83%. The results had pointed that the research carried through in the elaboration of the monographs of the egresses had had a diversity of methods, techniques, procedures, investigated public, places of the research, but the quantitative research is most recurrent. At first, one sends regards that the monograph is inserted in the sixth period of the course, for being part of a process in the construction to know.  Apart from is to salutar that this study it is used by other groups in the university and other institutions of superior education, to identify the trends searched in the area of the nursing, as well as displaying easinesses and difficulties in the elaboration of the monographs.